"TABOO ON MARRIAGE WITHIN THE SAME SURNAME IN BATAK TOBA SOCIETY: HISTORICAL ROOTS AND CURRENT RELEVANCE" - Amelia Anggi Owein Bintang; Azrina Hendri; Jesica Anastasia Lumbanraja; Flores Tanjung (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Marriage in the Batak Toba community occurs between clans. The exogamous marriage process, namely marriage outside the clan group, is the main characteristic of the Batak Toba community's marriage tradition. Therefore, the Toba Batak community strongly opposes marriage within the same clan, known as Namariboto, because it is considered incest. Traditionally, there are three marriage systems in the Batak community, namely exogamy, endogamy, and eleutrogamy. Of the three types, marriage within the same clan is included in the category that is prohibited by Batak customs and culture. Semarga Refers to the relationship between individuals who have a lineage through the father's line. In Yogyakarta, the Batak Mandailing community, who are migrants, have experienced a change in meaning related to Batak customary culture, shifting from an exogamous marriage system to an electrogamy system that does not recognize prohibitions like in the exogamy or endogamy systems. In Batak Toba customs, marriage within the same clan is considered taboo and prohibited. If the Batak Toba people perform a marriage of the same clan, they will violate customary norms and be considered Na So Maradat (people who do not understand customs). Those involved in a marriage of the same clan will be subject to sanctions according to the Batak Toba customary rules that are still in effect today.